DEVELOPMENT AND HISTORY OF NATIONAL CRAFTSMANSHIP IN UZBEKISTAN - Yuldashev, Salakhiddin (University Research Base, 2024)
The article examines the development and support of national crafts to the level of state policy. Opinions were expressed on the importance of legal and regulatory documents adopted by the President of Uzbekistan. The article highlights the relevance of the topic, scientific novelty, the measures taken to further develop the national handicrafts, the practical aspects of the problems that need to be addressed today. The Fergana Valley has long been one of the main centers of handicrafts in the region. the development of pottery, goldsmithing is covered.